2014
DOI: 10.1386/csfb.5.2.271_1
|View full text |Cite
|
Sign up to set email alerts
|

The Lula girl as ‘sublime and childlike’: nostalgic investments in contemporary fashion magazines

Abstract: Since the 1980s, the figure of the ‘girl’ has become one of the most prominent subject positions offered up in British fashion magazines (Jobling 1999). This way of constructing femininity harks back to the observation made by Roland Barthes, in 1967, that the rhetoric of fashion ‘reproduces, on the level of clothing, the mythic situation of Women in Western civilization, at once sublime and childlike’ (1990: 242). This article argues that both facets – the sublime and the childlike – continue to inform constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…For as Ros Coward states in relation to 1990s fashion photography: "it is no use trying to pretend that these child-like supermodels simply pander to male fantasies of resuming control and are being imposed on a resentful womanhood" (Coward as cited in Jobling 1999: 123). My analysis of niche fashion magazine Lula supports this claim (Laing 2014a). Lula is a publication brimming with images of the "woman-child" that nostalgically transport the reader back to her or his childhood.…”
Section: The "Woman-child" In Fashion Photographymentioning
confidence: 87%
See 1 more Smart Citation
“…For as Ros Coward states in relation to 1990s fashion photography: "it is no use trying to pretend that these child-like supermodels simply pander to male fantasies of resuming control and are being imposed on a resentful womanhood" (Coward as cited in Jobling 1999: 123). My analysis of niche fashion magazine Lula supports this claim (Laing 2014a). Lula is a publication brimming with images of the "woman-child" that nostalgically transport the reader back to her or his childhood.…”
Section: The "Woman-child" In Fashion Photographymentioning
confidence: 87%
“…In my own study I found that women had a range of different investments in the "woman-child": nostalgia for childhood (Laing 2014a); curiosity; intrigue; fascination; empowerment; comfort; aspiration; escape; identification with sadness; feminist critique; and so forth. Through reception studies I was able to "test out" theory on spectatorship -such as the idea of the "internalised male gaze" (Berger 2008(Berger [1972; Mulvey 2009Mulvey [1981) -much of which is speculative in nature.…”
Section: Investments In Fashion Photographymentioning
confidence: 97%
“…En su trabajo reciente, Morna Laing asegura que desde la década de 1980, la figura de la "niña" se ha convertido en una de las más importantes posiciones de las revistas de moda. Y afirma, siguiendo a Roland Barthes (1967) que esta forma de construir la feminidad mítica propia de occidente, a partir de lo sublime y lo infantil, se reproduce en las revistas de moda contemporáneas (Laing, 2014;2012). Laing analiza la revista Lula Girl como máximo exponente de este fenómeno.…”
Section: Hetero-tipografía Y La Hegemonía Discursivaunclassified
“…Elsewhere (Laing, 2012(Laing, , 2014 I have theorised childlike femininity in fashion photography as nostalgia for an idealised window of perfection: a state of being on the cusp between girlhood and womanhood; a no-place; 16 a liminal utopia that does not exist outside of representation. Yet, in images such as 'Sunny and Sexy' (Figures 2 and 3) by Miles Aldridge, the connotations of childhood are not utopian or nostalgic; instead, the freezing of time seems to violently disturb the woman pictured.…”
Section: Consumption Petulance and Deathmentioning
confidence: 99%
“…Yet unlike fashion spreads that reference Romantic childhood (Laing, 2012(Laing, , 2014, there is nothing nostalgic about Aldridge's imagery. Ashley Smith is not play-acting a child having fun; her expression is petulant, glazed-over or, at worst, disassociated: a mood completely at odds with the title, 'Sunny and Sexy'.…”
Section: Consumption Petulance and Deathmentioning
confidence: 99%